Globalization and non-traditional security issues : a study of human and drug trafficking in East Asia - Emmers, Ralf (2009)
East Asia faces a series of non-traditional security challenges that include environmental concerns, infectious disease and transnational crime. Rather than creating such forms of insecurity, the process of globalization has significantly amplified their spread and impact and accelerated their significance. This paper focuses on illicit drung and human trafficking in China and the Southeas Asian countries and examines these categories of transnational crime in the context of a globalizing world. It argues that the protection of state and human security against drug and people trafficking will increasingly require effective transnational cooperation and some surrendering of state sovereignty. The paper reflects on the depth of such problems in East Asia by analyzing the production, distribution and consumption of narcotics as well as the trafficking of women in the region. It notes an increasing level of multilateral cooperation in East Asia to combat human and drug trafficking. Yet, in addition to thte ongoing development of capacity-building and soft mechanisms of cooperation, deeper law enforcement and judiciary collaboration is required at a multileteral level to address these non-traditionl security challenges.